Current views on the diagnosis and treatment of genital lichen sclerosus - Pniewski, Tomasz; Smolarczyk, Katarzyna; Sałkowska-Wanat, Joanna M.; Majewski, Sławomir (Dermatology Review/Przegląd Dermatologiczny, 2016)
Lichen sclerosus (LS) is a chronic inflammatory disease of the skin and mucous membranes, which usually involves the genitals and anus. All patients with itchy symptoms from genitals or atrophic lesions, as well as indurations in this area, should be examined at least once by a physician experienced in the diagnosis and treatment of the diseases in the anogenital area. Early diagnosis and treatment of LS may reduce or prevent scarring within the lesion. In most cases the diagnosis is based on the typical clinical presentation. Diagnostic biopsies should be performed only under certain circumstances. The gold standard for the treatment of LS is the use of strong and very strong topical corticosteroids, but mild and moderate forms of the disease in males can be treated by surgical methods such as circumcision. It is necessary to avoid certain triggers that can cause the appearance of lesions.